Symptomatic and silent myocardial ischaemia in hypertensive patients with left ventricular hypertrophy. Issue 5 (May 1992) - Pringle, S D; Dunn, F G; Tweddel, A C; Martin, W; Macfarlane, P W; McKillop, J H; Lorimer, A R; Cobbe, S M
Abstract : OBJECTIVE--To assess the prevalence of symptomatic and silent myocardial ischaemia in patients with hypertensive left ventricular hypertrophy. DESIGN--Cross sectional study. SETTING--University department of medical cardiology. PATIENTS--90 patients (68 men and 22 women; mean age 57 (range 25 to 79)) with left ventricular hypertrophy due to essential hypertension. INTERVENTIONS--48 hour ambulatory ST segment monitoring (all patients), exercise electrocardiography (n = 79), stress thallium scintigraphy (n = 80), coronary arteriography (n = 35). RESULTS--43 patients had at least one episode of ST segment depression on ambulatory electrocardiographic monitoring. The median number of episodes was 16 (range 1 to 84) with a median duration of 8.6 (range 2 to 17) min. Over 90% of these episodes were clinically silent. 26 patients had positive exercise electrocardiography and 48 patients had reversible thallium perfusion defects despite chest pain during exercise in only five patients. 18 of the 35 patients who had coronary arteriography had important coronary artery disease. Seven of these patients gave no history of chest pain. CONCLUSIONS--Symptomatic and silent myocardial ischaemia are common in hypertensive patients with left ventricular hypertrophy, even in the absence of epicardial coronary artery disease.